Business tourism development: a portuguese perspective - Marques, Jorge; Santos, Norberto (Cuadernos de Turismo, 2017)
Over time, not only new leisure practices were developed but also new types of work, with globalization leading to a greater need for commercial, industrial and knowledge expansion, stimulating business travel. Therefore, long ago that tourism does not only refer on travel motivated by leisure and recreation. Travels motivated by business and professions, which consist of one of the oldest forms of travel, saw their “tourist status” officially recognized by the end of the twentieth century. Today, Business Tourism (also known as Meeting Industry) represents a significant role on local and regional economies and reveals a considerable potential for development. In this context, Destination Management Organizations (DMO), and more specifically Convention & Visitors Bureaus (CVB), play a key role in providing the structure associated with the territory and the management, planning and development of destinations, especially those who want to position themselves as Business Tourism destinations. This article aims to explore a few topics concerning the evolution of Business Tourism, its importance and context in Portugal.